The relative resistance of cassava cultivars to African Cassava Mosaic Disease (ACMD) as determined by two methods: ranksum and the area under the disease progress curve - Ariyo, O.A.; Dixon, A.G.O.; Atiri, G.I. (Informa UK Limited, 2002)
Twenty-five newly bred improved cassava cultivars, twenty-three improved from the International Institute of Tropical Agriculture and two local cultivars were evaluated for their relative resistance to African cassava mosaic begomovirus disease (ACMD) at Ibadan, in an area of high disease pressure representative of the forest/savanna transition zone of Nigeria. These cultivars were exposed to natural infection by the viruliferous whiteflies ( Bemisia tabaci Gennadius) and the Disease Incidence (DI) and index of symptom severity (ISS) were assessed for all clones. Results for the Rank-sum (i.e., sum of ranks for DI and ISS for each cultivar) and the area under the disease progress curve (AUDPC) were used to assess the relative resistance of the cassava clones. Those that showed low Rank-sum and AUDPC values were rated 'moderately resistant (MR)', 'resistant (R)', and 'highly resistant (HR)' to ACMD depending on their respective values and deviation from the mean distribution curve. Clones M94/0121 and 94/0239 were rated HR under the two methods. Clone M94/0583 was rated HR under the AUDPC with a deviation from the mean distribution curve of m 2.00 while it was rated R under the Rank-sum method with a deviation from the mean distribution of m 1.99. Also plants of clones ISU and TMS 30572 were rated highly infection (HS) under both methods. Clone TME-1 was intermediate between Moderately Resistant (MR) and Moderately Resistant (MS) under the AUDPC method with a deviation from the mean distribution of 0.00 but observed to be MS under the Rank-sum method with a deviation of + 0.2. The two methods of evaluation gave similar results as revealed by Spearman rank correlation ( r equals; 0.99, P <0.01). However, the AUDPC method is less cumbersome compared to the Rank-sum method. None of the clones was observed to be immune to the disease.